BCAT2 Shapes a Noninflamed Tumor Microenvironment and Induces Resistance to Anti‐PD‐1/PD‐L1 Immunotherapy by Negatively Regulating Proinflammatory Chemokines and Anticancer Immunity - Cai, Zhiyong; Chen, Jinbo; Yu, Zhengzheng; Li, Huihuang; Liu, Zhi; Deng, Dingshan; Liu, Jinhui; Chen, Chunliang; Zhang, Chunyu; Ou, Zhenyu; Chen, Minfeng; Hu, Jiao; et al. (Advanced science, 2023)
To improve response rate of monotherapy of immune checkpoint blockade (ICB), it is necessary to find an emerging target in combination therapy. Through analyzing tumor microenvironment (TME)‐related indicators, it is validated that BCAT2 shapes a noninflamed TME in bladder cancer. The outcomes of multiomics indicate that BCAT2 has an inhibitory effect on cytotoxic lymphocyte recruitment by restraining activities of proinflammatory cytokine/chemokine‐related pathways and T‐cell‐chemotaxis pathway. Immunoassays reveal that secretion of CD8+T‐cell‐related chemokines keeps a robust negative correlation with BCAT2, generating a decreasing tendency of CD8+T cells around BCAT2+ tumor cells from far to near. Cotreatment of BCAT2 deficiency and anti‐PD‐1 antibody has a synergistic effect in vivo, implying the potential of BCAT2 in combination therapy. Moreover, the value of BCAT2 in predicting efficacy of immunotherapy is validated in multiple immunotherapy cohorts. Together, as a key molecule in TME, BCAT2 is an emerging target in combination with ICB and a biomarker of guiding precision therapy. By multiomics analysis, experiment validation and cohort comparison, it is found that BCAT2 is a potential combination therapy target in immunotherapy. Inhibition of BCAT2 can transform a noninflamed tumor microenvironment (TME) to an inflamed TME by regulating secretion levels of CD8+T‐cell‐related chemokines. Furthermore, it is also a potential predictive biomarker of efficacy of immunotherapy.